2017
DOI: 10.1293/tox.2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methotrexate exposure on medaka (<i>Oryzias latipes</i>) testes

Abstract: For the purpose of clarifying the histopathological effects of methotrexate (MTX) on medaka testes, wild-type and homogenic p53-deficient male medaka at 4 to 6 months post-hatching were exposed to 0.25 mg/ml of MTX for 96 h with histopathological examination of testes at 24, 48, 72 and 96 h. At 72 and 96 h after the start of MTX exposure, numerous apoptotic cells were observed in the spermatogonia and spermatocytes, and the pyknotic cell rate and the TUNEL-positive and cleaved caspase-3-positive rates in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Bcl‐2 helps in the regulation of antioxidant pathways and cell defenses against lipid oxidation without affecting the intracellular ROS levels, which demonstrate its powerful antioxidant effects indirectly. Previous research also has indicated that MTX causes oxidative stress and induces testicular tissue damage, including degeneration of the seminiferous tubules and germ‐cell apoptosis, as well as activating the p53 ‐signaling pathway, which is associated with the mitochondrial cell death cascade (Hirako et al, 2017; Sheikhbahaei et al, 2016; Sherif et al, 2020). The antiapoptotic activity of Se has been reported in numerous studies, confirming that it inhibits apoptosis by affecting apoptotic pathways such as Bax, p53 , and caspase‐3 (Chen et al, 2013; Chen et al, 2014; Rahbardar et al, 2021; Yeo & Kang, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl‐2 helps in the regulation of antioxidant pathways and cell defenses against lipid oxidation without affecting the intracellular ROS levels, which demonstrate its powerful antioxidant effects indirectly. Previous research also has indicated that MTX causes oxidative stress and induces testicular tissue damage, including degeneration of the seminiferous tubules and germ‐cell apoptosis, as well as activating the p53 ‐signaling pathway, which is associated with the mitochondrial cell death cascade (Hirako et al, 2017; Sheikhbahaei et al, 2016; Sherif et al, 2020). The antiapoptotic activity of Se has been reported in numerous studies, confirming that it inhibits apoptosis by affecting apoptotic pathways such as Bax, p53 , and caspase‐3 (Chen et al, 2013; Chen et al, 2014; Rahbardar et al, 2021; Yeo & Kang, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the drug's contraindication for pregnant women due to the risk of miscarriage and birth abnormalities, the paternal influence of MTX on their offspring was largely unknown. In addition to this, the vast majority of studies in fish models such as medaka and zebrafish has been performed during embryological stages [57][58][59][60] , while few have evaluated the effect on adults 61 and the consequences on their offspring.…”
Section: M5c Modifications Are Increased By Methotrexatementioning
confidence: 99%